Comparison of Microstructural Properties of One- and Two- Part Fly Ash Geopolymer Concretes - Nurulhuda, Nadziri; Idawati, Ismail; Amirul Syahmi, Ardi; Nurul Hadirah, Damni; Annisa, Jamali (2022)
Geopolymerisation is a chemical process involving reacting raw aluminosilicate minerals with alkali activators such as sodium hydroxide and potassium hydroxide to produce a geopolymer binder. In most cases, anhydrous activator is typically made by dilution with water to form a liquid activator before being blended with other raw components such as sand and coarse aggregates. This traditional approach, also known as two-part mixing, can be hazardous due to the corrosive nature of the liquid activator, making it difficult to mix huge volumes of concrete. In recent years, a one-part mix or “just add water” geopolymer concrete has been proposed as a simpler mixing method to minimise mixing time and improve the perception of geopolymer concretes. Similar to the preparation of typical Portland cement concretes, a one-part mix is performed in which all of the dry ingredients, including the solid activator, are initially combined together before water is eventually added to the mix. As a result, the aim of the research is to compare these two geopolymer concrete types, as well as how these mixing processes affect the mechanical strength and microstructural properties of fly ash geopolymer concretes. This study also compares the effects of the activators used, which included sodium hydroxide (NaOH) and potassium hydroxide (KOH). Microstructural investigation was performed through Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy (SEM-EDX). It was observed that one-part geopolymer concrete using NaOH as activator shows higher mechanical strength. The fly ash geopolymer binder study reveals that sodium aluminosilicate hydrate (N-A-S-H) gels and potassium aluminosilicate hydrate (K-A-S-H) gels are the binding gels formed in one-part and two-part mixing methods at different alkali activators with the formation of N-A-S-H gels is faster with NaOH activator than with KOH. It may be inferred that one-part geopolymer concretes perform better than two-part geopolymer concrete mixtures, and that NaOH activated concretes exhibit more desired characteristics than KOH activated concretes. It can be concluded that one-part geopolymer concretes perform better compared to two-part mix of geopolymer concretes and NaOH-activated concretes gives desirable properties compared than KOH.